Official state records: A minefield for studying pre-1957 Malay women - Mahani Musa, (Universiti Kebangsaan Malaysia, 2008)
In Southeast Asia, studies on women in history has been a very recent phenomenon. The unavailability of primary sources has been cited for the lack of historical research on women. Quite often the national history pushed women to the margins while the women’s socioeconomic and political role is seen as supplementary to men. In Malaysia, the focus on women studies is limited. Unlike Chinese women, the study on Malay women’s involvement in politics was more popular due to the availability of the sources and little is known of their socioeconomic contributions. Kedah provides us with a more clearer picture of the role played by Malay women in the socioeconomic development in the state through various documentary materials, including the records of the Stamp Office, the Land office, the State Secretariat, the annual report of the state administration, report on education and medical report and the law known as Undang-Undang Kedah 1893